1996
DOI: 10.1097/00000539-199607000-00020
|View full text |Cite|
|
Sign up to set email alerts
|

Twenty-Four of Twenty-Seven Studies Show a Greater Incidence of Emesis Associated with Nitrous Oxide than with Alternative Anesthetics

Abstract: All obtainable investigations that have compared the incidence of vomiting in groups of patients who received nitrous oxide (N2O) and in patients who received anesthetics or analgesics without N2O were examined for a single, dichotomous variable: whether patients who received N2O experienced an absolutely higher incidence, as distinct from a statistically significantly higher incidence, of vomiting. The null hypothesis is that N2O has no effect on emesis, such that an increased incidence of vomiting should occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Therefore, in this study, fentanyl citrate (1 mcg kg −1 ) was added to 8% sevoflurane during induction. Previous studies have demonstrated that sevoflurane, N 2 O and intraoperative opioid use increased the incidence of PONV (13)(14)(15)(16). The administration of midazolam and high concentration O 2 has been reported to reduce the incidence of PONV (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in this study, fentanyl citrate (1 mcg kg −1 ) was added to 8% sevoflurane during induction. Previous studies have demonstrated that sevoflurane, N 2 O and intraoperative opioid use increased the incidence of PONV (13)(14)(15)(16). The administration of midazolam and high concentration O 2 has been reported to reduce the incidence of PONV (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Watcha et al [21], an investigation by Larsson et al [8] revealed a lower incidence of emetic episodes in the propofol group despite the use of nitrous oxide (5%) compared to thiopentone and halothane (27%). It might be that omitting nitrous oxide in the propofol group would have led to a more excessive reduction of vomiting in the present study [27,28]. However, we chose to use nitrous oxide in our investigation in order to reduce the risk of awareness and to supply additive analgesia to propofol and inhalational anesthesia [28].…”
Section: P-valuementioning
confidence: 94%
“…Omission of N 2 O significantly reduced PONV in several meta-analyses, [10][11][12][13] but the risk of intraoperative awareness was also increased. 12 In most meta-analyses, propofol was associated with a lower frequency of PONV when used for total iv anesthesia in the absence of N 2 O.…”
Section: Résultats : Aucune Différence Intergroupe N'a éTé Enregistrémentioning
confidence: 95%